Cathair Crobh Dearg: From Ancient Beliefs to the Rounds 2017 - Frédéric Armao (Estudios Irlandeses, 2017)
This paper will study the case of the stone enclosure of Cathair Crobh Dearg, Co. Kerry (also referred to as the City) and Dá Chích Anann (or the Paps of Anu), the twin mountains that can be seen from the enclosure. The site is mentioned in ancient mythological texts as well as more modern accounts in connection with the Irish festival of Bealtaine, in early May. The author relied on archaeological evidence, an analysis of ancient documents, a number of manuscripts from the Irish National Folklore Collection, as well as personal visits to the site in order to try and understand the nature, and possibly origin, of both contemporary rituals and ancient beliefs.